Green Cities? Urbanization, Trade and the Environment - Rainald Borck; Michael P. Pflüger (Institute for the Study of Labor (IZA), 2015)
This paper establishes a simple theoretical framework which comprises key forces that shape the structure and interrelation of cities to study the interdependencies between urban evolution and the environment. We focus on the potential of the unfettered market forces to economize on emissions. A key finding is that these forces alone may suffice to generate an urban Environmental Kuznets Curve. In particular, reducing trade costs increases per capita incomes and generates a U-shaped evolution of emissions in the process of agglomeration and redispersion. Another key result is that agglomeration per se is typically not a boon for the environment, as total emissions in the total city system are likely to rise.
Keywords: F18; Q50; R11; R12; 330; city structure; city systems; environmental pollution; global warming; Environmental Kuznets Curve; trade costs; commuting costs; housing